Historical reviews of the assessment of human cardiovascular function: interrogation and understanding of the control of skin blood flow - David. A. Low; Helen Jones; N. Tim Cable; Lacy M. Alexander; W. Larry Kenney (European Journal of Applied Physiology, 2020)
Several techniques exist for the determination of skin blood flow that have historically been used in the investigation of thermoregulatory control of skin blood flow, and more recently, in clinical assessments or as an index of global vascular function. Skin blood flow measurement techniques differ in their methodology and their strengths and limitations. To examine the historical development of techniques for assessing skin blood flow by describing the origin, basic principles, and important aspects of each procedure and to provide recommendations for best practise. Venous occlusion plethysmography was one of the earliest techniques to intermittently index a limb’s skin blood flow under conditions in which local muscle blood flow does not change. The introduction of laser Doppler flowmetry provided a method that continuously records an index of skin blood flow (red cell flux) (albeit from a relatively small skin area) that requires normalisation due to high site-to-site variability. The subsequent development of laser Doppler and laser speckle imaging techniques allows the mapping of skin blood flow from larger surface areas and the visualisation of capillary filling from the dermal plexus in two dimensions. The use of iontophoresis or intradermal microdialysis in conjunction with laser Doppler methods allows for the local delivery of pharmacological agents to interrogate the local and neural control of skin blood flow. The recent development of optical coherence tomography promises further advances in assessment of the skin circulation via three-dimensional imaging of the skin microvasculature for quantification of vessel diameter and vessel recruitment.

The effect of 48 weeks of aerobic exercise training on cutaneous vasodilator function in post-menopausal females - Gary J. Hodges; Lisa Sharp; Claire Stephenson; Ashish Y. Patwala; Keith P. George; David F. Goldspink; N. Tim Cable (European Journal of Applied Physiology, 2010)

Reliability of maximal muscle force and voluntary activation as markers of exercise-induced muscle damage - James Peter Morton; Greg Atkinson; Donald PM MacLaren; Nigel Tim Cable; Gareth Gilbert; Caroline Broome; Anne McArdle; Barry Drust (European Journal of Applied Physiology, 2005)

Eccentric exercise, isokinetic muscle torque and delayed onset muscle soreness: the role of reactive oxygen species - Graeme L. Close; Tony Ashton; Tim Cable; Dominic Doran; Don P. M. MacLaren (European Journal of Applied Physiology, 2004)